The Confederate jurist : the legal life of Judah P. Benjamin - Gilmore, William C. (Edinburgh : Edinburgh University Press, 2021)
This is the first biography written from a legal perspective on the public life of Judah P. Benjamin (1811-1884); a prominent figure in the common law world in the second half of the 19th century. Drawing on a range of primary source materials including newspaper articles, case law and extensive archival research in the UK and USA, it charts his rise as a lawyer first in the mixed legal system of Louisiana and then nationally.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 6, 2021).
Keywords: Benjamin, J. P. -- 1811-1884.; Jewish lawyers -- United States -- Biography; Jewish lawyers -- England -- Biography; Lawyers -- United States -- Biography; Lawyers -- England -- Biography; Jewish statesmen -- Confederate States of America -- Biography; Statesmen -- Confederate States of America -- Biography; Biography; Biography & non-fiction prose